2021
DOI: 10.1038/s41415-021-3369-1
|View full text |Cite
|
Sign up to set email alerts
|

Fallow time determination in dentistry using aerosol measurement in mechanically and non-mechanically ventilated environments

Abstract: AGPs can be carried out in open bay environments with a minimum of six air changes per hour of mechanical ventilation.Four-handed dentistry with high-volume suction and a saliva ejector are essential mitigating factors during AGPs.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…35 A study by Noordien et al (2021) reported that aerosol contamination among dental professionals was reduced by 53% when a high-volume evacuator and a low-volume saliva ejector were used together compared to when only a low-volume saliva ejector was used. 36 A study by Shahdad et al (2021) investigated the level of aerosol particle counts 1 h after dental aerosol-generating procedures (AGPs), such as scaling operations, and found that the number of particles decreased by opening the window and using mechanical ventilation after AGP. 37 In the case of physical hazards, 27.8% of participants were at high risk and 51.5% were at medium risk, with 46.8% found to be high-risk individuals of "musculoskeletal pain," the highest among all items (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…35 A study by Noordien et al (2021) reported that aerosol contamination among dental professionals was reduced by 53% when a high-volume evacuator and a low-volume saliva ejector were used together compared to when only a low-volume saliva ejector was used. 36 A study by Shahdad et al (2021) investigated the level of aerosol particle counts 1 h after dental aerosol-generating procedures (AGPs), such as scaling operations, and found that the number of particles decreased by opening the window and using mechanical ventilation after AGP. 37 In the case of physical hazards, 27.8% of participants were at high risk and 51.5% were at medium risk, with 46.8% found to be high-risk individuals of "musculoskeletal pain," the highest among all items (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…36 A study by Shahdad et al (2021) investigated the level of aerosol particle counts 1 h after dental aerosol-generating procedures (AGPs), such as scaling operations, and found that the number of particles decreased by opening the window and using mechanical ventilation after AGP. 37 In the case of physical hazards, 27.8% of participants were at high risk and 51.5% were at medium risk, with 46.8% found to be high-risk individuals of "musculoskeletal pain," the highest among all items (Figure 2). As a dental hygienist is an occupation with a high risk of musculoskeletal pain, 38,39 repetitive and static scaling works put a strain on the muscles and joints of the worker.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is not suitable to be used in all procedures and some patients ( Matys and Grzech-Leśniak, 2020 ). There were some studies evaluating the influence of EOS, and they found EOS was effective in reducing droplets ( Chavis et al, 2021 , Ehtezazi et al, 2021 , Graetz et al, 2021 , Makhsous et al, 2021 , Senpuku et al, 2021 , Shahdad et al, 2021 , Yang et al, 2021 ). A vitro study showed using IOS was effective by 88 % in reducing aerosol compared to other groups.…”
Section: Introductionmentioning
confidence: 99%
“…Also, they found using high and low suction minimized the aerosol level, and EOS reduced it further down the baseline reading ( Yang et al, 2021 ). However, most of these study ( Chavis et al, 2021 , Ehtezazi et al, 2021 , Graetz et al, 2021 , Shahdad et al, 2021 , Yang et al, 2021 ) was performed in vitro but still it is need more investigations in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Methods used to minimize the spread of bacteria, viruses, and aerosols in dental practice include preoperative mouth gargling, rubber-barrier isolation, and the use of personal protective equipment, air filtration equipment, and mechanical ventilation [13][14][15][16][17], which all reduce the production and spread of aerosols, but are less efficient at removing aerosols. It has also been shown that aerosols spread quickly and in high concentrations in relatively closed oral treatment rooms [7], so it is urgent to study the dispersion and adsorption of aerosols generated during the oral treatment procedures.…”
Section: Introductionmentioning
confidence: 99%